Trinidad and Tobago : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
KEY ISSUES The economy is embarking on sustainable growth, but the main challenge will be to boost long-run growth by structural reforms and reorienting fiscal policy. Supply-side slowdowns in the energy sector are ending, while available evidence suggests non-energy growth is robust and economic slack is being used up. Non-energy growth should settle around a long-term 2-2 1\2 percent per annum rate, while new energy sector investment may begin to bear significant fruit over the medium term. Headline inflation is trending down (in part for statistical reasons), while core inflation remains moderate. Domestic risks are to the upside. The main medium-term external risk would be a sustained decline in energy prices. With excess capacity in the labor market significantly diminished, the time is drawing near for policy tightening. Although ad hoc measures will reduce the budget deficit this fiscal year, the underlying baseline suggests a growing overall imbalance and unsustainable debt accumulation on unchanged policies, although the authorities have announced their intention to pursue fiscal consolidation. The CBTT will have to carefully consider how to tighten the monetary stance given high excess bank liquidity. Sustainable growth requires re-configuring fiscal policy, although achieving this will be challenging for the time being in view of national elections due in 2015. Ad hoc measures should be replaced with policies that durably improve non energy-based revenues and spending. The proceeds from extracting non-renewable resources should be saved and invested as a stepping stone to lasting prosperity. Fuel subsidies need to be curtailed and social programs rationalized. Non-energy sector tax bases should be broadened and tax expenditures limited. Greater flexibility is needed in the foreign exchange market. Despite sizable reserves, foreign exchange shortages, which impose unnecessary economic costs, have recurred. There is no concrete evidence of either a parallel market or arrears on foreign exchange, and the CBTT has recently sold foreign exchange with the objective to clear the market, but a recurrence of the situation could indicate the existence of an exchange restriction. The CBTT can address the problem through increased flexibility in the foreign exchange system. Structural reforms are underway, but more are needed to foster a diversified economic base. Financial sector reform is advancing, including expanding the CBTT's regulatory perimeter to systemically important non-bank financial institutions. Recent streamlining of regulations that have hampered business activity is welcomed, but needs to be further advanced. Government operations are increasingly hamstrung by a poorly functioning civil service. Perceptions of corruption can be reduced by adopting a transparent procurement process. Programs that mask underemployment should be replaced with more effective training. Growing statistical shortcomings have rendered the conduct of surveillance ever harder, and must be addressed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet